2015
DOI: 10.1007/s10295-015-1643-4
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of Paenibacillus polymyxa LY214, a camptothecin-producing endophytic bacterium from Camptotheca acuminata

Abstract: Camptothecin (CPT) is mainly produced and extracted from Camptotheca acuminata and Nothapodytes foetida for pharmaceutical use, i.e., the starting material for chemical conversion to the clinical CPT-type drugs. As the third largest plant anticancer drug, the heavy demand on CPT from global market leads to many research efforts to identify new sources for CPT production. Herein we report the isolation and characterization of a CPT-producing endophytic bacterium Paenibacillus polymyxa LY214 from Camptotheca acu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 17 publications
(17 reference statements)
1
7
1
Order By: Relevance
“…Previous works on the CAM-producing endophytes suggested that CAM production will be attenuated with subsequent successive subculturing and fermentation (Pu et al 2013;Pu et al 2015). A similar CAM production attenuation was observed when the C. acuminata cell suspension cultures were successively subcultured and grown in the same axenic conditions ( Supplementary Fig.…”
Section: Cam Production Attenuation and Cryopreservation Of The Cell supporting
confidence: 55%
See 1 more Smart Citation
“…Previous works on the CAM-producing endophytes suggested that CAM production will be attenuated with subsequent successive subculturing and fermentation (Pu et al 2013;Pu et al 2015). A similar CAM production attenuation was observed when the C. acuminata cell suspension cultures were successively subcultured and grown in the same axenic conditions ( Supplementary Fig.…”
Section: Cam Production Attenuation and Cryopreservation Of The Cell supporting
confidence: 55%
“…The heavy demand for CAM derivatives has resulted in destructive harvesting of C. acuminata, the CAM-producing plant in China, and it was claimed to be a protected plant species in China (http:// www.gov.cn/gongbao/content/2000/content_60072.htm). Thus, identifying new sources of CAM and novel production methods are urged in the science community (Bhalkar et al 2016;Deepthi and Satheeshkumar 2016;Pu et al 2013;Pu et al 2015;Vasanthakumari et al 2015;Venugopalan and Srivastava 2015;Venugopalan et al 2016).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…192 The production of camptothecin ( 26 ) by the endophyte Paenibacillus polymyxa LY214 could be enhanced 30× by the addition of secologanin, tryptamine and XAD-16. 193 Polyene antifungals are of difficult isolation due to their amphiphilic nature. 194 A new method was devised for the isolation of amphotericin B ( 27 ) analogues and of truncated amphotericin B biosynthesis intermediates by the use of XAD-16, which considerably improved the recovery of 27 derivatives from culture media.…”
Section: Facing the Challenges In The Isolation Of Hydrophilic Compoundsmentioning
confidence: 99%
“…In the introduction to their paper in 2015, Pu et al gave a short history of reports of endophytic microbes that could produce camptothecin on isolated culture [57], but in almost all cases, the yields decreased with subculture. However, they had reported 2 years earlier that one of their isolates, Trichoderma atrovide LY357, did show increased yields when elicitors/adsorbent resins were added to the culture broth [58].…”
Section: Supplementation Studies With Camptothecinproducing Endophytesmentioning
confidence: 99%